DOP30 Factors associated with life satisfaction in people with Crohn's disease and ulcerative colitis: results from the national 2018 Crohn's and Colitis UK Inflammatory Bowel Disease Quality of Life Survey. (25th January 2019) - Rowse, G; Hollobone, S; Afhim, S; Oliver, P
Abstract: Background: Crohn's disease and ulcerative colitis have a negative impact on health-related quality of life (HRQoL). HRQoL is valued by patients as a 'real-world' measure of how illness impacts their day-to-day lives, going beyond direct measures of health status. Life satisfaction is a vital component of subjective HRQoL and one of the three indicators of well-being, also adversely impacted by inflammatory bowel disease (IBD). Evaluation of the factors associated with low life satisfaction in IBD may identify possible targets amenable to intervention, to improve well-being and HRQoL. The aim of this study was to identify the key factors associated with life satisfaction in a large sample of people with IBD. Methods: Participants were invited to complete a survey, administered online and via post to members and supporters of the charity Crohn's and Colitis UK. The survey was designed to assess seven hallmarks of HRQoL, and was informed by theory of change, patient and wider IBD community priorities. The hallmarks included understanding IBD, maintaining well-being, feeling in control, overcoming stigma and reducing isolation. Exploratory χ 2 analyses were conducted to examine the factors associated with life satisfaction, including disease, demographics, and psychological variables. Results: After data cleaning, 8061 participants with IBD were included (response rate 22.2%, mean age 45.3 years, SD 16.4). The majority of respondents were female (F, 69.2%) and had Crohn's disease (CD, 78.5%). Low satisfaction with life was identified in 11.9% of respondents. Analyses identified significant relationships between low life satisfaction and disease type (CD 13.2%, ulcerative colitis 7.1%, p < 0.001); disease activity (active 18%, remission 6.6%, p < 0.001); ethnicity (White British 11.6%, Asian, Black, Mixed, or Other ethnic group 16.4%, p < 0.05); perception of control over disease ( p < 0.001); coping ( p < 0.001); feeling left out ( p < 0.001); feeling involved in care ( p < 0.001); understanding own disease ( p < 0.001); and experiencing stigma ( p < 0.001). No significant association was found for gender (F 12%, male 11.8%, p = 0.281). Conclusions: In a large sample of participants with IBD, low life satisfaction was associated with disease characteristics (CD; active disease); individual characteristics (ethnicity); and psychological constructs (sense of control; coping; loneliness; involvement in care; understanding; perceived stigma). The psychological constructs may be amenable to intervention and support. There is the need to improve public understanding of IBD to limit the stigma felt by those with the diagnosis. Modelling of the current data and longitudinal data collection would aid our understanding of the relationships between the key variables over time.